Holistic methodology for characterisation of the thermally induced failure of commercially available 18650 lithium ion cells. Issue 39 (4th May 2017) - Lammer, Michael; Königseder, Alexander; Hacker, Viktor
Abstract : A highly effective method of investigating complex thermal degradation scenarios on Li-ion cells has been developed to promote battery safety. Abstract : An innovative approach to holistic analysis of thermally induced battery failure has been developed. A purpose-built test rig with high reproducibility within the specific setup produces reliable experimental data. Thermal ramp experiments at a defined state of charge are conducted on three types of commercial lithium ion batteries of the 18650 format. Thermally induced cell break-down is detected by temperature measurement on the cell surface. These failure scenarios comprise the venting of gas and particles and the exothermic process of thermal runaway. The tests showed heat emissions of up to 31 kJ during the final phase, with the battery surface reaching up to 877 °C. The release of gas is continuously logged and analysed by micro-GC. The main components are flammable and, due to the high concentration of CO of up to 61.4%, highly toxic. The maximum total gas emission during the deflagration of the cell was 5495 cm 3 .